1999
DOI: 10.1111/j.1749-6632.1999.tb09366.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Modes of Action of the Imidazoline Compound RX871024 in Pancreatic β‐Cells: Blocking of K+ Channels, Mobilization of Ca2+ from Endoplasmic Reticulum, and Interaction with Exocytotic Machinerya

Abstract: The imidazoline compound RX871024 glucose-dependently potentiates the release of insulin in pancreatic islets and beta-cell lines. This activity of the compound is not related to its action by stimulating alpha 2-adrenoceptors and I1- and I2-imidazoline receptors. There are at least three modes of action of RX871024 in beta-cells: (1) RX871024 blocks the ATP-dependent, Ca(2+)-activated, and delayed rectifier K+ channel activity; (2) RX871024 causes mobilization of Ca2+ from thapsigargin-sensitive intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…In addition, we have demonstrated that long-term exposure to the imidazoline compound RX871024 is not toxic to ␤-cells. These data, together with the observations published previously (3)(4)(5)(6)(7)42), suggest that imidazoline compounds should be explored as potential therapeutic agents for the treatment of both type 1 and type 2 diabetes. …”
Section: Imidazolines Protect Against Apoptosismentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, we have demonstrated that long-term exposure to the imidazoline compound RX871024 is not toxic to ␤-cells. These data, together with the observations published previously (3)(4)(5)(6)(7)42), suggest that imidazoline compounds should be explored as potential therapeutic agents for the treatment of both type 1 and type 2 diabetes. …”
Section: Imidazolines Protect Against Apoptosismentioning
confidence: 86%
“…Previously, we showed that imidazolines stimulate insulin release both by blocking ATP-dependent K + channels, with a subsequent increase in cytoplasmic free Ca 2+ concentration ([Ca 2+ ] i ), and by directly affecting the exocytotic machinery (3,7). In addition, imidazoline compounds induce release of Ca 2+ from nonmitochondrial thapsigargin-sensitive intracellular stores (8).…”
mentioning
confidence: 99%
“…Second, measurements of protein phosphorylation in permeabilized insulin-secreting HIT T15 cells show that RX871024 induced protein phosphorylation (24). Finally, the increase in phosphorylation induced by the imidazoline was blocked by the protein kinase inhibitors RpBrcAMPS, H-89, and staurosporine (24). Thus, the imidazoline RX871024 induced insulin secretion not only by depolarizing the membrane and increasing [Ca 2ϩ ] i , but also by stimulating PKA-and PKC-dependent protein phosphorylation in pancreatic ␤-cells.…”
mentioning
confidence: 97%
“…First, inhibitors of protein kinase A (PKA) (H-89 and Rp-BrcAMPS) or protein kinase C (PKC) (calphostin C and staurosporine) completely abolished imidazoline-induced increases in insulin secretion, whereas glucose-and KClinduced stimulation of insulin secretion were unaffected (18). Second, measurements of protein phosphorylation in permeabilized insulin-secreting HIT T15 cells show that RX871024 induced protein phosphorylation (24). Finally, the increase in phosphorylation induced by the imidazoline was blocked by the protein kinase inhibitors RpBrcAMPS, H-89, and staurosporine (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation